Postnatal Pancraniosynostosis in a Patient with Infantile Hypophosphatasia. (November 2016) - Nahabet, Edward H.; Gatherwright, James; Vockley, Jerry; Henderson, Nadene; Tomei, Krystal L.; Grigorian, Adriana P.; Kaminski, Beth; Bass, Nancy; Selman, Warren R.; Lakin, Gregory E.
Hypophosphatasia is a rare metabolic bone disorder that predisposes patients to craniosynostosis. Typically, patients born with hypophosphatasia will exhibit fused cranial sutures at birth. This is the first reported case of delayed onset of pancraniosynostosis in a patient with infantile hypophosphatasia. The severity of onset and delayed presentation in this patient are of interest and should give pause to those care providers who treat and evaluate patients with hypophosphatasia.